Effect of cardiac resynchronization therapy on the risk of ventricular tachyarrhythmias in patients with chronic kidney disease. Issue 3 (15th September 2016) - Daimee, Usama A.; Biton, Yitschak; Moss, Arthur J.; Zareba, Wojciech; Cannom, David; Klein, Helmut; Solomon, Scott; Ruwald, Martin H.; McNitt, Scott; Polonsky, Bronislava; Wang, Paul J.; Goldenberg, Ilan; et al.
Abstract : Background: The effect of chronic kidney disease (CKD) on benefit from cardiac resynchronization therapy with defibrillator (CRT‐D) in reducing ventricular tachyarrhythmia (VTA) risk among mild heart failure (HF) patients is not well understood. Methods: We evaluated the impact of baseline renal function on VTAs in 1274 left bundle branch block (LBBB) patients enrolled in MADIT‐CRT. Two prespecified subgroups were created based on estimated glomerular filtration rate (GFR): GFR <60 ( n = 413) and GFR ≥60 ml/min/1.73 m 2 ( n = 861). Primary end point was ventricular tachycardia/ventricular fibrillation/death (VT/VF/death). Secondary end points were any VT/VF and ventricular tachycardia ≥ 200 bpm or VF (fast VT/VF). Results: There were 413 (32%) LBBB patients presenting with CKD, primarily of moderate severity (GFR mean 48.1 ± 8.3). For patients with and without CKD, CRT‐D was associated with lower risk of the primary end point (GFR<60: HR = 0.61, 95% CI: 0.41–0.89, p = .010; GFR≥60: HR = 0.58, 95% CI: 0.52–0.89, p = .005), relative to ICD‐only treatment. For patients in both renal function categories, CRT‐D in comparison to ICD alone was associated with lower risk of VT/VF (GFR<60: HR = 0.68, 95% CI: 0.42–1.10, p = .113; GFR≥60: HR = 0.65, 95% CI: 0.48–0.88, p = .005) and fast VT/VF (GFR<60: HR = 0.49, 95% CI: 0.25–0.96, p = .038; GFR≥60: HR = 0.55, 95% CI: 0.39–0.80, p = .001), when accounting for competing mortality risk. This effect was independent of CRT‐induced reverse remodeling. Conclusion: Among mild HF patients with LBBB, those with and without CKD both derived benefit from CRT‐D in risk reduction in VTAs, independent of cardiac reverse remodeling.